Analysis of Energy Consumption in Colombia Using the Holt Method - Contreras-Salinas, Jheison; Lopez, Fernando; Rondon-Rodriguez, Carlos A; HernÃ¡ndez Palma, Hugo g; De-la-Hoz-Hernandez, Juan-David (International Journal of Energy Economics and Policy, 2020)
Energy production is constantly facing major challenges today, because despite initiatives to promote the insertion of renewable energy, electricity consumption has shown considerable growth in recent years. In order to use an instrument that facilitates forecasts and predictive processes for the design of strategic plans associated with energy management, the application of the Holt Method is proposed using data on electricity demand in Colombia, GDP per capita and industrial value added, making an analysis of the last 10 years, based on figures from the World Bank. The final results predict that energy consumption for the period 2018 - 2020 will be between 66,231 GWk and 66,885 GWk. Keywords: Energy Consumption, Holt Method, Energy Efficiency, Colombia. JEL Classifications: D24; Q43; M31. DOI: https://doi.org/10.32479/ijeep.8221